KAPASITAS ANGGOTA DEWAN DALAM MENDORONG PERCEPATAN PEMBANGUNAN DAERAH - Iskandar, Sentot (Majalah Bisnis & IPTEK, 2021)
Reformation era is the starting point in the Indonesian decentralization policy change toward real. Where previously the areas are so restrictive and not memilikim any authority in doing pembanguanan region, now in the era of reform through Act No. 22 of 1999 , the region has the freedom and initiative to manage their own regions. Substantial changes in this Act is the separation of the Regional Government of the Council (Article 14 of Law No. 22 of 1999) that previously integrated integrally. This separation is a manifestation of political decentralization which gives the political space in Parliament and society that fosters sekaliguas Democratization process at the local level. With these changes should have transparency and accountability in the region is expected to further improve. Keywords: regional development; bureaucratic reform